Brain Capillary Ultrastructure in Idiopathic Normal Pressure Hydrocephalus: Relationship With Static and Pulsatile Intracranial Pressure - Eidsvaag, Vigdis Andersen; Hansson, Hans-Arne; Heuser, Kjell; Nagelhus, Erlend A.; Eide, Per K. (Journal of neuropathology and experimental neurology, 2017)
Abstract Idiopathic normal pressure hydrocephalus (iNPH) is a neurodegenerative disease of unknown cause. We investigated the morphology of capillaries in frontal cortex biopsies from iNPH patients and related the observations to overnight intracranial pressure (ICP) scores. A biopsy (0.9×10 mm) was taken from where the ICP sensor subsequently was inserted. Brain capillaries were investigated by electron microscopy of biopsies from 27 iNPH patients and 10 reference subjects, i.e. patients (not healthy individuals) without cerebrospinal fluid circulation disturbances, in whom normal brain tissue was removed as part of necessary neurosurgical treatment. Degenerating and degenerated pericyte processes were identified in 23/27 (85%) iNPH and 6/10 (60%) of reference specimens. Extensive disintegration of pericyte processes were recognized in 11/27 (41%) iNPH and 1/10 (10%) reference specimens. There were no differences in basement membrane (BM) thickness or pericyte coverage between iNPH and reference subjects. The pulsatile or static ICP scores did neither correlate with the BM thickness nor with pericyte coverage. We found increased prevalence of degenerating pericytes in iNPH while the BM thickness and pericyte coverage did not differ from the reference individuals. Observations in iNPH may to some extent be age-related since the iNPH patients were significantly older than the reference individuals.